Thermodynamic Study on the Interaction Between Tl(I) Ion and L-Alanine - AGHAIE, M.; KESHAVARZ REZAEI, F.; ZARE, K.; AGHAIE, H. (Asian Journal of Chemistry, 2010)
The formation constant of interaction of Tl(I) ion with L-alanine was experimentally studied at pH = 4.1 ± 0.01 (50 mM of potassium hydrogen phthalate buffer), ionic strength of 0.1 M potassium nitrate at 5 different temperatures 15, 20, 25, 30 and 35 °C by UV-Vis spectrophotometric method. The optical absorption spectra of mixtures containing considered cation and L-alanine were analyzed by using SQUAD software, in order to obtain the formation constant and the stoichiometry of respect complex. The best fitting of present results showed that the 1:1 complex in respect to the studied system (Tl+(aq) + L-alanine) is formed. Regarding the values of formation constant at different temperatures and using Van’t Hoff equation, it is possible to calculate the respective thermodynamic functions of formation such as ΔG°, ΔH°, ΔS° of the studied complex.